Performance and emissions characteristics of alternative biodiesel fuel on 4-stroke marine diesel engine - Nursal, Ridwan Saputra (2015)
Alternative fuels for diesel engines have become increasingly important due to several socioeconomic aspects, imminent depletion of fossil fuel and growing environmental concerns. Global warming concerns due to the production of greenhouse gases (GHGs) such as carbon dioxide (CO2) as results from internal combustion engine have seen as one of major factor the promotion of the use of biofuels. Therefore, the use of biodiesel fuel (BDF) as an alternative for fossil diesel (DSL) is among the effective way to reduce the CO2 emission since it is classified as green and renewable energy. However, it is acknowledged that the use of BDF is restricted due to loss of efficiency and long term problems upon the engine. Hence, a study focussed on investigating the effects of BDF derived from crude palm oil (CPO), jatropha curcas oil (JCO) and waste cooking oil (WCO) blended with DSL at various blending ratio on engine performance and exhaust gas emissions has been performed. This experimental test was done using a small 4-stroke marine diesel engine which operates through engine speeds stimulated at 800, 1200, 1600 and 2000 rpm under 0, 50 and 90% dynamometer loads integrated with emission gas analyser that attached to the exhaust pipeline. As results of experimental investigations, the increment in performance of torque, brake power, brake thermal efficiency (BTE) and brake mean effective pressure (BMEP) while decrease in brake specific fuel consumption (BSFC) has been observed for CPO and JCO fuels comparative to DSL. Meanwhile a contrariwise outcome was obtained for WCO fuels. In conjunction, CPO and JCO promotes lower carbon monoxide (CO) emissions but signified higher nitrogen oxides (NOx), carbon dioxide (CO2) and hydrocarbon (HC) emissions compared to DSL. Apart, WCO promotes lower CO, CO2 and HC emissions but signified higher NOx emissions compared to DSL. It can be concluded that BDF is useable in diesel engines without engine modifications. The outcomes of this study is significantly contributed as a guidence and reference to the local authority in order to evaluate and select the suitable and optimum BDF for development of policies, regulations and standard.